Konflik Yuridiksi Dalam Perkawinan Campuran: Studi Perbandingan Choice Of Law Antara Indonesia Dan Belanda - Muhammad Razib; Rizky Muzib Hidayat; M. Fahmi Al Amruzi; Anwar Hafidzi (SPT. haria Journal and Education Center Publishing, 2026)
Mixed marriages between Indonesian citizens and foreign nationals have become increasingly common in the era of globalization. However, they also create legal problems, particularly conflicts of jurisdiction and uncertainty in determining the applicable law (choice of law), especially when different legal systems, nationalities, and values are involved. This study aims to examine and compare the legal systems governing mixed marriages in Indonesia and the Netherlands in order to assess the extent to which both countries provide legal certainty and protection for the parties involved. This research uses a qualitative method with a library research approach through the analysis of legislation, academic literature, and relevant previous studies. The findings show that Indonesia still relies on the principle of nationality (lex patriae) and religious law, while lacking a comprehensive choice of law mechanism. This condition may lead to legal uncertainty regarding marital property, children’s status, and citizenship. In contrast, the Netherlands adopts a more flexible approach by allowing parties to determine the applicable law while emphasizing equality and human rights protection. Therefore, legal reform in Indonesia is necessary to create a more adaptive system for transnational legal relations.